2018
DOI: 10.1515/geochr-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Low to middle Pleistocene paleoclimatic record from the Kraków-Częstochowa Upland (Poland) based on isotopic and calcite fabrics analyses

Abstract: The quality of paleoenvironmental reconstruction based on speleothem records depends on the accuracy of the used proxies and the chronology of the studied record. As far as the dating method is concerned, in most cases, the best solution is the use of the U-series method to obtain a precise chronology. However, for older periods (i.e., over 0.5 Ma), dating has become a serious challenge. Theoretically, older materials could be dated with the U-Pb dating method. However, that method requires a relatively high u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…By using oxygen isotope stratigraphy (OIS) method, it was found that this flowstone crystallizing process was dated between 935 ±5 ka -470 ±5 ka with three major discontinuities. The observed isotopic variability was also consistent and confirmed with the petrographic observations of the flowstone (Błaszczyk et al, 2018). The visitors come back to the entrance opening by the same way (Fig.…”
Section: Głęboka Cavesupporting
confidence: 87%
“…By using oxygen isotope stratigraphy (OIS) method, it was found that this flowstone crystallizing process was dated between 935 ±5 ka -470 ±5 ka with three major discontinuities. The observed isotopic variability was also consistent and confirmed with the petrographic observations of the flowstone (Błaszczyk et al, 2018). The visitors come back to the entrance opening by the same way (Fig.…”
Section: Głęboka Cavesupporting
confidence: 87%
“…An explanation for this is that the permafrost conditions prevailed around [57] and beneath [58] the former Fennoscandian Ice Sheet, thereby preventing speleothem growth [17] because there was no water movement in the frozen ground. This hypothesis is indirectly supported by a recent study showing flowstone deposition in the Kraków-Częstochowa Upland at 975-470 ka BP [59]), predating the major glaciations in the region. The thawing of this frozen ground could be a prolonged process after deglaciation [60], maintaining unfavorable conditions for speleothem formation.…”
Section: Spatial Distribution Of Speleothem Recordsmentioning
confidence: 68%
“…In addition, there is a good chance to further extend the regional dataset beyond MIS 6, as records predating the ones in SISAL_v1 have already been identified from Turkish [69], Macedonian [51], Croatian [78] and Hungarian [79] localities. Moreover, calcareous cave deposits exceeding the current limit of applicability of U-Th dating method (~600 kyr) and for which U-Pb dating methods [80,81] could be applied, have been found in the region [59]. The average length of the records is ~13.8 kyr and the median is 4.9 kyr, including hiatuses.…”
Section: Temporal Distribution Of Speleothem Recordsmentioning
confidence: 99%
“…One explanation for this is that the permafrost conditions which existed around [56] and beneath the former Fennoscandian Ice Sheet which covered this area [57] very likely prevented speleothem formation (see also [23]) of because there was no water movement in the frozen ground. This hypothesis is indirectly supported by a recent study showing flowstone deposition in the Kraków-Częstochowa Upland at 975-470 ka [58]), predating the major glaciations of the region. The thawing of this frozen ground could be a prolonged process after deglaciation [57,59], maintaining unfavorable conditions for speleothem formation.…”
Section: Distribution Of Speleothem Isotopic Records In Space and Timementioning
confidence: 70%
“…Croatian [70] and Hungarian [71] localities. Moreover, calcareous cave deposits exceeding the current limit of applicability of U-Th dating method can be found in the region [58]. However, recently this knowledge-gap began to be filled by speleological monitoring studies becoming abundant in the region [10,[74][75][76][77][78][79][80].…”
Section: Distribution Of Speleothem Isotopic Records In Space and Timementioning
confidence: 99%